Self-rectifying resistive switching characteristics of Ti/Zr3N2/p-Si capacitor for array applications. Issue 15 (1st August 2021) - Bae, Dongjoo; Lee, Doowon; Jung, Jinsu; Kim, Sungho; Kim, Hee-Dong
Abstract: In this study, we present a self-rectifying resistive switching property observed in Ti/Zr3 N2 / p- Si and Ti/Zr2 N/ p- Si metal-insulator-semiconductor (MIS) capacitors for array applications. Compared to the Zr2 N film, the Zr3 N2 film has a higher trap density due to weaker bonding energy and a higher trap generation rate. In the experimental results for the Zr3 N2 sample, we observed a higher on/off ratio, a larger read margin, more stable retention, and more stable DC cycling. In addition, both the trap concentrations increased at the LRS compared to of the common HRS, which was a result of analyzing the nitride trap density (Nnt ) within the Zrx Ny film and an interface trap (Nit ) between the Zrx Ny and the p- Si layers. Particularly, it is found in the Zr3 N2 film that the Nnt is rapidly increased, which results in an increased current ratio and an increased read margin.